2023
DOI: 10.3390/foods12142699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Freeze-Dried Grape Pomace on Fresh Tagliatelle Gluten Network and Relationship to Sensory and Chemical Quality

Abstract: The incorporation of 5 and 10% freeze-dried grape pomace powder (GPP) in fresh tagliatelle pasta preparation was evaluated for its effect on chemical composition, gluten protein structure, and sensory properties. The addition of the freeze-dried GPP led to a significant increase (p < 0.05) in polyphenol content in the raw and cooked fortified pasta samples with respect to 100% semolina pasta, although the phenolic content decreased after the cooking process. The opposite phenomenon was observed with the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Among the fortified food, pasta is the most preferred item because it is very simple to be prepared, it has good sensory properties and is recognized as a staple food [ 23 ]. Although pasta fortified with by-products has been abundantly studied and various types of recovered powders were explored in the last years to investigate the correlation among technological features, chemical characteristics, and sensory properties [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], little research is reported in the literature to verify the ability of by-products to prolong fresh pasta shelf life. Information is available on extracts from broccoli by-products [ 10 ] or pomegranate peel powder, both applied to fresh ravioli [ 14 ], which are a special type of filled pasta.…”
Section: Introductionmentioning
confidence: 99%
“…Among the fortified food, pasta is the most preferred item because it is very simple to be prepared, it has good sensory properties and is recognized as a staple food [ 23 ]. Although pasta fortified with by-products has been abundantly studied and various types of recovered powders were explored in the last years to investigate the correlation among technological features, chemical characteristics, and sensory properties [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], little research is reported in the literature to verify the ability of by-products to prolong fresh pasta shelf life. Information is available on extracts from broccoli by-products [ 10 ] or pomegranate peel powder, both applied to fresh ravioli [ 14 ], which are a special type of filled pasta.…”
Section: Introductionmentioning
confidence: 99%